The Giving of Liquid Organic Fertilizer (LOF) for Growth And Yield of The Peanut (Arachis Hypogaea L.) in Sandy Tailing Post-Tin Mining - Lintang Arum Gayatri; Ratna Santi; Deni Pratama (xxxx-xxxx, 2023)
Gayatri  LA, Santi R, Pratama D.  2022.  The giving of liquid organic fertilizer (LOF) for growth and yield of the peanut (Arachis Hypogaea L.) in Sandy Tailing Post-Tin Mining. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 327-336.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Efforts to expand the peanut planting area in Bangka can be by optimizing the use of suboptimal land such as sandy tailing post tin mining. Application of pineapple skin liquid organic fertilizer (LOF) is one of the ingredients that can improve the properties of sandy soil as a medium for plant growth. This research aimed to know the effect of pineapple skin liquid organic fertilizer to growth and yield of peanut in post-tin mining land. This research was conducted in the post-mining tin land Reclamation Air jangkang PT Timah Tbk, Merawang District, Bangka Regency. This research used a Randomied block Design (RBD) with control NPK Phonska 15:15:15 (P0), POC 35 mL (P1),POC 65 mL (P2), POC 95 mL (P3), POC 125 mL (P4), and  (POC 150 mL (P5 and repeated 4 times. The data was analyzed by using the F test with 95% significant level, then proceed with the LSD test α = 95%. The results show that the liquid organic fertilizer of pineapple skin did not gave significant effect on the growth and yield of peanut plants with an-organic fertilizer. It show that application of liquid organic fertilizer pineapple skin has potential to replace the usage of NPK Phonska 15:15:15 in post-tin mining land The best concentration for yield of peanut was highest dose 35 mL.